Management of the refractory vitiligo patient: current therapeutic strategies and future options - Wang, Xinju; Wu, Wei; Chen, Jianru; Li, Chunying; Li, Shuli (Frontiers in Immunology, 2024)
Vitiligo is an autoimmune disease that leads to disfiguring depigmented lesions of skin and mucosa. Although effective treatments are available for vitiligo, there are still some patients with poor responses to conventional treatment. Refractory vitiligo lesions are mostly located on exposed sites such as acral sites and lips, leading to significant life stress. Understanding the causes of refractory vitiligo and developing targeted treatments are essential to enhance vitiligo outcomes. In this review, we summarized recent treatment approaches and some potential methods for refractory vitiligo. Janus kinase inhibitors have shown efficacy in refractory vitiligo. A variety of surgical interventions and fractional carbon dioxide laser have been widely applied to combination therapies. Furthermore, melanocyte regeneration and activation therapies are potentially effective strategies. Patients with refractory vitiligo should be referred to psychological monitoring and interventions to reduce the potential pathogenic effects of chronic stress. Finally, methods for depigmentation and camouflage may be beneficial in achieving uniform skin color and improved quality of life. Our ultimate focus is to provide alternative options for refractory vitiligo and to bring inspiration to future research.